Assessment of Service Quality at the Credit Cooperative: A SERVQUAL and Importance-Performance Analysis Approach - Wurjaningrum, Febriana; Lenga, Karolina Wako (Jurnal Manajemen dan Perbankan (JUMPA), 2025)
In the competitive financial sector of Indonesia, the expansion of savings and loan Cooperatives, exemplified by the Sangosay Credit Cooperative established in 1983, faces challenges in retaining members and meeting their service expectations, particularly due to increasing competition from online lending platforms. This research investigates the service quality of Sangosay Credit Cooperative by utilizing the SERVQUAL framework, focusing on nineteen attributes based on five service quality dimensions. A qualitative approach was employed, involving a questionnaire distributed to 100 participants. The findings reveal that the services provided do not fully align with member expectations, as evidenced by gap scores ranging in reliability and in tangibles. The analysis highlighted notable deficiencies between the cooperative's offerings and member expectations, particularly in reliability, responsiveness, empathy, assurance, and tangibles. Critical areas for improvement identified include the timeliness of services, transaction simplicity, staff accountability, communication skills, and overall operational efficiency. The study recommends several actionable strategies, such as regular employee performance evaluations, comprehensive training programs, member feedback surveys, and enhanced customer service strategies to elevate service quality and better serve the cooperative's members. Abstrak - Dalam lanskap keuangan Indonesia yang kompetitif, pertumbuhan Koperasi simpan pinjam, seperti Koperasi Kredit Sangosay yang didirikan pada tahun 1983, menghadapi tantangan dalam mempertahankan anggota dan memenuhi harapan layanan mereka, terutama karena meningkatnya persaingan dari platform pinjaman daring. Penelitian ini menyelidiki kualitas layanan Koperasi Kredit Sangosay dengan memanfaatkan kerangka kerja SERVQUAL, dengan fokus pada sembilan belas atribut berdasarkan lima dimensi kualitas layanan. Pendekatan kualitatif digunakan, yang melibatkan kuesioner yang dibagikan kepada 100 peserta. Temuan tersebut mengungkapkan bahwa layanan yang diberikan tidak sepenuhnya selaras dengan harapan anggota, sebagaimana dibuktikan oleh skor kesenjangan dalam reliability dan dalam tangibles. Analisis tersebut menyoroti kekurangan penting antara penawaran koperasi dan harapan anggota, khususnya dalam reliability, responsiveness, empathy, assurance, dan tangibles. Area utama yang teridentifikasi untuk perbaikan meliputi ketepatan waktu layanan, kesederhanaan transaksi, akuntabilitas staf, keterampilan komunikasi, dan efisiensi operasional secara keseluruhan. Studi ini merekomendasikan beberapa strategi yang dapat ditindaklanjuti, seperti evaluasi kinerja karyawan secara berkala, program pelatihan yang komprehensif, survei umpan balik anggota, dan strategi layanan pelanggan yang ditingkatkan untuk meningkatkan kualitas layanan dan melayani anggota koperasi dengan lebih baik.